A Research Study on Prompt Results and Physical Assessment of Mechanically Ventilated Children - Raheel Farooq Butt, Neelam Khan, Sana Khan, Amna Akbar, Sarosh Khan Jadoon, Areeba Tanveer (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: There is alarming information on the usage of MV in PICUs from Asian nations. The goals of this research were to identify the patients' clinical profiles, traits, frequent causes of breathing problems, complications connected to ventilation problems, and ultimate outcomes. For admittance to the pediatric critical care unit, the criterion for mechanical ventilation (MV) is rigorous (ICU). It may be difficult to manage children in impoverished nations with minimal resources that need invasive ventilation. Methods: The information gathered included epidemiological trends, ventilation indications, problems, duration of use of the ventilator, and results. From January 2022 to December 2022, a retrospective analysis of kids who needed ventilator support in the Liaqaut National Hospital, Karachi was conducted. Results: The most frequent indications for ventilation in this research were impending respiratory arrest (34.6%) and a low Glasgow coma rating (17.8%). Of the 1172 patients who were brought to the PICU, 101 (8.6%) needed mechanical ventilation. 75% of the patients on mechanical ventilation were male, and 42% were newborns. We discuss the epidemiological patterns, prevalence, causes, and results of pediatric intensive care unit ventilator support cases. Planning better treatment plans in the future may assist improve outcomes, which can be achieved by analysis of this data. The average MV lasted 2.1 days. These kids had a 38.6% death rate. Conclusions: In summary, there is little MV activity in our PICU. The most frequent justification for mechanical ventilation was respiratory failure. Keywords: Respiratory Failure, Mechanically Ventilated, Pediatrics Intensive Care Unit.